Correlation of tri-ponderal mass index with insulin-like growth factor-I and insulin-like growth factor binding protein-3 in children and adolescents - Iee Ho Choi; Sun-Young Kim; Minsun Kim (Annals of Pediatric Endocrinology & Metabolism, 2024)
Purpose We aimed to investigate the relationship between the tri-ponderal mass index (TMI), a new indirect measure of fat mass, and insulin-like growth factor (IGF)-I/IGF binding protein (IGFBP)-3. Methods The study included 1,630 children and adolescents who visited Jeonbuk National University Children's Hospital. Each patient’s medical record was retrospectively reviewed for age, sex, height, weight, body mass index (BMI), TMI, and IGF-1 and IGFBP-3 levels. Study participants were divided by sex and then categorized by age, BMI, and TMI. Finally, the correlations of TMI with IGF-1 level, IGF-1 standard deviation score (SDS), IGFBP-3 level, IGFBP-3 SDS, and IGF-1/IGFBP-3 ratio were investigated. Results All participants were <19 years of age. BMI correlated with IGF-1 and IGFBP-3 levels in both sexes; however, the relationship with TMI differed by sex. TMI correlated with IGF-1 and IGFBP-3 SDS in boys and with IGF-1, IGFBP-3, and IGFBP-3 SDS in girls across all ages. In boys, BMI and TMI significantly correlated with IGF-1, IGF-1 SDS, IGFBP-3, IGFBP-3 SDS, and the IGF-1/IGFBP-3 ratio in the normal-weight group. TMI also correlated with IGF-1, IGFBP-3, and IGFBP-3 SDS in the overweight group. In girls, BMI significantly correlated with IGF-1, IGF-1 SDS, IGFBP-3, IGFBP-3 SDS, and the IGF-1/IGFBP-3 ratio in the normal-weight group and with IGFBP-3 and IGFBP-3 SDS in the overweight group, while TMI correlated with IGF-1, IGF-1 SDS, and the IGF-1/IGFBP-3 ratio in the normal-weight group; with IGF-1, IGFBP-3, and IGFBP-3 SDS in the overweight group; and with IGFBP-3 SDS in the obese group. Conclusions TMI may more strongly correlate with IGFBP-3 level than BMI in overweight boys and with IGFBP-3 SDS in overweight and obese girls. The correlation of IGFBP-3 SDS with TMI may be helpful for evaluating weight status in adolescent girls.